Efektivitas Kebijakan Pengelolaan Dana Bantuan Operasional Sekolah (BOS) ( Studi SD Negeri Ganggangpanjang Kabupaten Sidoarjo) - Hanindyah Fajrun Nuristighfar; Hendra Sukmana (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2022)
This study aims to analyze the effectiveness of school operational assistance management. The method in this research is descriptive qualitative. The type of data used in this study is qualitative data consisting of primary and secondary data. The research was conducted at the Ganggangpanjang State Elementary School in the 2019-2021 academic year. Sources of data obtained through library research are available online and offline, such as scientific journals, books, and news from trusted sources. In addition, data sources were also obtained from interviews with school principals, treasurers, and the 2019-2021 RKAS report archive. The study results indicate that managing the school's operational assistance funds has been effective. However, the facilities and infrastructure have not shown any effectiveness. In addition, the availability of student activity unit space is still integrated with the teacher's room; as a result, student health support has not been adequate. On the one hand, there is strict supervision carried out by the office of cultural education and the school committee so that the realization is by receiving school operational assistance funds.